2000
DOI: 10.1073/pnas.97.7.2999
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of enterohemorrhagic Escherichia coli O157 prevalence in feces, hides, and carcasses of beef cattle during processing

Abstract: A survey was performed to estimate the frequency of enterohemorrhagic Escherichia coli O157:H7 or O157:nonmotile (EHEC O157) in feces and on hides within groups of fed cattle from single sources (lots) presented for slaughter at meat processing plants in the Midwestern United States, as well as frequency of carcass contamination during processing from cattle within the same lots. Of 29 lots sampled, 72% had at least one EHEC O157-positive fecal sample and 38% had positive hide samples. Overall, EHEC O157 preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

34
489
11
9

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 675 publications
(543 citation statements)
references
References 22 publications
(23 reference statements)
34
489
11
9
Order By: Relevance
“…High prevalences of EHEC O157 in bovine faeces, 27.8% in United State [7], 19.7% in the United Kingdom [2] and 16.1% in the Czech Republic [4], have been shown previously. In Japan, it was previously reported that the isolation rate of EHEC O157 was 0.3% in faecal samples from slaughterhouse cattle in 1987 [11], 1.4% in faeces and 0.3% of dressed carcasses in 1996 [22], and 6.5% in faeces in 1999 [15].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…High prevalences of EHEC O157 in bovine faeces, 27.8% in United State [7], 19.7% in the United Kingdom [2] and 16.1% in the Czech Republic [4], have been shown previously. In Japan, it was previously reported that the isolation rate of EHEC O157 was 0.3% in faecal samples from slaughterhouse cattle in 1987 [11], 1.4% in faeces and 0.3% of dressed carcasses in 1996 [22], and 6.5% in faeces in 1999 [15].…”
mentioning
confidence: 94%
“…In particular, it is often isolated from faeces of cattle showing no clinical signs of disease. It was reported that the prevalence of EHEC O157 in cattle was 0.2-28% in the United States [7,8,23], 1.9% in Australia [5], and 4.2-20% in Europe [2,4,9,16]. Therefore, cattle can harbour the organisms in their faeces and are regarded as a natural reservoir and source of infection [3].…”
mentioning
confidence: 99%
“…Transmission of E. coli O157:H7 from cattle to humans occurs via foodborne and waterborne routes (3)(4)(5). Although E. coli O157:H7 strains occur in other animals, cattle have the highest known prevalence (1,2,6). Therefore, knowledge of the ecologic relationship between E. coli O157:H7 and its bovine reservoir host is critical to understanding the epidemiology of the disease and ultimately to the rational development of programs to eliminate the organism from cattle.…”
mentioning
confidence: 99%
“…C attle are a major reservoir for enterohemorrhagic Escherichia coli O157:H7 strains, which cause hemorrhagic colitis and hemolytic uremic syndrome (HUS) in humans (1)(2)(3). Transmission of E. coli O157:H7 from cattle to humans occurs via foodborne and waterborne routes (3)(4)(5).…”
mentioning
confidence: 99%
“…A presença da bactéria na faca dos manipuladores durante a evisceração mostra que este objeto não está sendo esterilizado de maneira corret, conforme designa a circular N o 175/2005, do MAPA, que preconiza a esterilização das facas por 20 segundos a 82ºC, no mínimo, após cada operação, pois durante a evisceração pode ocorrer uma contaminação da carcaça mais extensa por conteúdo gastrointestinal (Brasil, 2005). Elder et al (2000) também indicaram que o processo de evisceração é um ponto crítico de controle para a contaminação das carcaças, e estratégias de intervenção devem ser implementadas.…”
Section: Resultados E Discussão Ocorrência De Escherichia Coliunclassified